(untitled) (Vietnam Journal of Community Medicine, 2024)
Patients who survive cardiac arrest often develop severe neurological dysfunction due to hypoxic brain injury and reperfusion-induced cell death. Therapeutic hypothermia has become a standard therapy for cerebral protection following the successful return of spontaneous circulation in patients with out-of-hospital cardiac arrest, according to American Heart Association guidelines. This is a case report of a 21-year-old patient who developed in-hospital cardiac arrest and was revived after prolonged cardiopulmonary resuscitation. Therapeutic hypothermia was then established with local measures for 24 hours for cerebral protection. The patient was gradually and successfully weaned off of the ventilator with no neurological impairment. There is increasing evidence of therapeutic hypothermia and its protective mechanisms in patients with non-shockable arrest rhythms, with particular emphasis on neurological outcomes. This article emphasizes the role of therapeutic hypothermia in every successful cardiopulmonary resuscitation, irrespective of the cardiac rhythm.